Development of the simulation model for shooting motion in water polo (summary) - Nakayama, Y.; Nakashima, M.; Takagi, H. (Japanese Journal of Sciences in Swimming and Water Exercise, 2011)
During shooting motion in water polo, the shooter is subjected to the fluid force. Therefore, through the use of the fluid force generated by moving upper limb and lower limb, it is important to keep own balance and deliver enough power to the ball. If we can analyze the dynamics of the shooting motion considering the fluid force and the interaction between the shooter and the ball, findings to increase the ball speed will be found out. The objective of this study was to develop the simulation model of shooting motion in water polo. For the objective, we constructed the simulation model and conducted experiment to obtain the data of shooting motion. We conducted a simulation by inputting experimental data into the simulation model and validated the model. As the result, this model was found to be effective.